Strengthening Academic Hardiness Through Self-Reflection-Based Narrative Counseling: A Single-Case Research - Muhammad Muhajirin; Agung Nugraha; Rima Irmayanti; Anandha Putri Rahimsyah; Adelia Lintang Anjarika (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to examine the effectiveness of self-reflection-based narrative counseling in strengthening academic hardiness among senior high school students who demonstrate low academic persistence and difficulties in coping with academic challenges. Methodology: This study employed a single-case research design using an A–B format. Three (n = 3) senior high school students were selected through purposive sampling based on low academic hardiness scores. The intervention consisted of five individual self-reflection–based narrative counseling sessions. Data were collected using an academic hardiness scale administered during the baseline, intervention, and three-week follow-up phases. Data were analyzed using descriptive visual analysis to examine changes in level, trend, and stability of academic hardiness across phases. Main Findings: The results indicated a clear and consistent increase in academic hardiness across all three participants during the intervention phase compared to the baseline condition. Improvements were observed in the dimensions of commitment, control, and challenge, and were maintained at the three-week follow-up, suggesting a sustained positive effect of the intervention. Novelty/Originality of this study: This results indicated a clear and consistent increase in academic hardiness across all three participants during the intervention phase compared to the baseline condition. Improvements were observed in the dimensions of commitment, control, and challenge, and were maintained at the three-week follow-up, suggesting a sustained positive effect of the intervention.